(untitled) (Revista Contexto & Saúde, 2022)
Objective: to test the association of SB and moderate to vigorous physical activity (MVPA) with body mass index (BMI) in a representative sample of Brazilian young people. Methods: This is a cross-sectional school-based study (n = 1,023), including adolescents (14-21y; 54% female) from public and private schools in a Brazilian city. The survey was conducted in 2015 and the adolescents self-reported SB (screen time) and MVPA. Height and body mass were measured to calculate BMI. Quantile regression was used to investigate the association between SB, MVPA and BMI distribution percentiles (P10 ..., P90; statistical significance p <.01). Results: SB and MVPA were associated with higher and lower BMI values, respectively. Quantile regression revealed that the associations were nonlinear and stronger in the upper BMI percentiles. Also, in the adjusted models (SB and MVPA in the same model), the associations were enhanced for MVPA. For example, each additional hour of MVPA at P10 was associated with −0.05 (p <.01) lower BMI value, against −0.09 at P50 (p <.01) and even lower at P90, −0.24 (p <.01). Conclusion: SB and MVPA were independently and nonlinearly associated with BMI in our sample of Brazilian youth. The associations were more notable in the higher percentiles of the BMI distribution. Our findings suggest that nonlinearity between exposures and outcome should be considered when proposing future strategies for pediatric obesity prevention.